Optimising the Decarboxylation of Anacardic Acid by Exploring the Temperature Effects - Eva G. Nyoni; Petro E. Mabeyo; Aldo J. Kitalika (Journal of Chemistry)
Cashew nut shell liquid (CNSL) is one of the raw materials extracted from cashew nut shells (CNS). This liquid can be processed to produce cardanol through the decarboxylation of anacardic acid, a significant isolate from CNSL. The decarboxylation process involves heating anacardic acid to a favourable reaction temperature. This study investigated the ideal temperature required for this process. Fourier-transform infrared (FTIR) spectroscopy characterised CNSL and cardanol isolates. Anacardic acid was separated, purified and heated to temperatures ranging from 140°C to 152°C after being isolated from CNSL. At each temperature, the decarboxylation yield was calculated. The results indicated that a temperature of 145°C is optimal for the decarboxylation of anacardic acid at standard pressure, with a maximum yield of 66% observed. These findings contrast with other studies, which suggested optimal temperatures of 140°C and 180°C–200°C for the decarboxylation of anacardic acid. The main advantage of the identified temperature in the anacardic acid decarboxylation reaction is the increased yield and overall process efficiency by promoting the synthesis of desired products over potential side reactions (selectivity). Furthermore, reactions at lower temperatures can be more energy-efficient than those at higher temperatures, thus reducing costs in industrial processes. Lastly, it is generally safer to work with lower temperatures, as there is a reduced risk of thermal degradation and thermal runaway reactions.